Nécropoles protohistoriques du Sénonais Serbonnes / La Créole' Michery / La Longue Raie' Soucy / Mocques Bouteilles (Yonne) - Baray, Luc; Deffressigne, Sylvie; Leroyer, Chantal; Villemeur, Isabelle (Documents d'archéologie française, 1994)
This volume presents the first result of archaeolagical work carried out during the construction of the A5 and the Al 60 Melun- Troyes motorways. Three protohistoric burialgrounds, situated between Montereau and Sens, form the subject of a publication following several lines; as well as a comparative study of the structures and small finds there is usefid information about the funeral rites and the methods of inhumation. These are the combined results of a complementary approach between archaeologists, anthropologists and pollen specialists. The presentation of these sites is followed by a study of the population of Burgundy from the late Bronze age to the Iron âge.